STUDENT SATISFACTION LEVEL WITH THE BIOLOGY PROGRAM - Cruz-Neyra, Lidia (2017)
In the process of educational quality, several higher education institutions have shown concern for the satisfaction of their students, in order to know their expectations and opinion of the various parameters of the study, development and improvement plans, according to the evaluation or self-assessment models. Th e present work was carried out with the purpose of knowing how satisfi ed students are with the Biology degree at Ricardo Palma University, Lima, Peru. Such as the sequence of courses, teaching methodology, basic and specialty training, content of subjects, teaching strategies, subject assessment, library use, learning and performance. A survey was designed and applied to 63 students from the 7th to the 9th academic year in the semester 2015-II, whose results are presented generally in the categories, level of percentage satisfaction index Th e analysis of the information determined that 67% of the students are satisfi ed with the 2006-II curriculum, being their best appreciation in the achievements and performances with respect to the area of biodiversity, and their lower satisfaction in the area of ecology and environment; Th is indicates that a revision of the curricular plans and improvements in the respective plan are needed.